The Transformation of Receptive to Productive Skills: An Analysis of Reading Experience in the Production of Narrative Texts of High School Students - Moh Mahrus Shofi; Nor Afni Dian Maulidini; Ulil Absor R.S.D; Yanti Linarsih (Molang: Journal Islamic Education, 2026)
Reading and writing are two essential dimensions inextricably intertwined in the process of language acquisition and mastery, where reading operates as a receptive cognitive process and writing as a productive cognitive process. Although previous literature has largely proven a positive correlation between these two skills at the primary and vocational education levels, the transition of reading experiences into the skill of producing complex narrative texts at the Senior High School (SMA) level has not been comprehensively explored. This study aims to deeply analyze how reading experience affects the cognitive and linguistic abilities of high school students in developing the structure, plot, and vocabulary richness in narrative text production. The research method applied is qualitative with a Literature Review approach that examines ten recent relevant journal articles. The synthesis results from various literature confirm that reading interest and reading habits consistently serve as a crucial foundation in facilitating idea generation and enriching students' active vocabulary repertoire. In the specific context of high school students, the depth and variety of reading experiences directly correlate with high-level cognitive abilities to compose narratives that are more coherent, logical, and rich in stylistic language. The readability level of teaching materials is also found to be a determinant factor in determining the quality of input that will be transformed into written output. The conclusion of this study asserts that without an adequate and challenging literacy ecosystem, the capacity for advanced narrative text production in high school students will experience stagnation, thus requiring pedagogical interventions that fully integrate analytical reading activities with creative writing practices.